2017
DOI: 10.1038/am.2017.51
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic protective effect of a BN-carbon separator for highly stable lithium sulfur batteries

Abstract: Lithium sulfur (Li-S) batteries have drawn much attention as next-generation batteries because of their high theoretical capacity (1672 mAh g − 1), environmental friendliness and low cost. However, several critical issues, which are mainly associated with the polysulfide shuttling effect, result in their poor electrochemical performance. Carbon-modified separators have been introduced to attempt to address these systemic challenges. However, this approach focused only on the suppression of dissolved polysulfid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 34 publications
3
90
0
4
Order By: Relevance
“…The SEM image indicates ar ough and uneven surfacem orphology (Figure 6c). [18] These results strongly support that nano-MnO 2 effectively aids to curb the diffusion of polysulfide towardsl ithium foil, thereby protecting the lithium from side reactions and improving the cycle performance of Li-S batteries. The XPS spectrum of the PC/S shows two peaks centereda tS 2p 3/2 (162 eV) and S2p 3/2 (161 eV), which corresponds to ac hemical shift indicating Li 2 S 2 and Li 2 S( Figure S5).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…The SEM image indicates ar ough and uneven surfacem orphology (Figure 6c). [18] These results strongly support that nano-MnO 2 effectively aids to curb the diffusion of polysulfide towardsl ithium foil, thereby protecting the lithium from side reactions and improving the cycle performance of Li-S batteries. The XPS spectrum of the PC/S shows two peaks centereda tS 2p 3/2 (162 eV) and S2p 3/2 (161 eV), which corresponds to ac hemical shift indicating Li 2 S 2 and Li 2 S( Figure S5).…”
Section: Resultsmentioning
confidence: 53%
“…The polysulfide solutionw as prepared by followingr eported study. [18] During discharge, the polysulfide species diffused out of PC/S electrode migrated towards the anodic side withouta ny blocking, whereas the polysulfides dissolved out of M-PC/S were chemically captured by nano-MnO 2 (Figure 5a and b). [18] During discharge, the polysulfide species diffused out of PC/S electrode migrated towards the anodic side withouta ny blocking, whereas the polysulfides dissolved out of M-PC/S were chemically captured by nano-MnO 2 (Figure 5a and b).…”
Section: Resultsmentioning
confidence: 99%
“…[62] The formation of the stable SEI on the Li anode contributed to the uniform plating/strippingo fL ia ss hown in Figure7a, b). [67] In 2018, Chen et al reported the coating of 2D MoN x ,w hich had desirable properties to immobilize PSs intermediates, onto the normal separator in LSBs. [68] The shuttle effect was suppressed with this lightweight 2D materiala nd achieved up to 572 mAh g À1 capacity at 1C.T he flexibility of the PP wasr etained with more homogenous Li deposition.…”
Section: D Nitride/phosphide-based Interlayers/ Separator Additivesmentioning
confidence: 99%
“…Working on similar substrates, Wu et al developed a functional coating for commercial separators based on boron‐doped reduced GO . Han et al reported the synthesis of a boron‐ and nitrogen‐doped reduced GO‐based porous carbon materials, while Kim et al coated boron nitride and carbon powder together on a conventional separator using a doctor blade . Chen et al reported the synthesis of a nitrogen and sulfur co‐doped porous carbon material with a graphene backbone .…”
Section: A Summary Of Recent Literature On Li‐s Battery Separators CLmentioning
confidence: 99%